2009
DOI: 10.1091/mbc.e09-03-0203
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Ductal Morphogenesis and the Pdx1 Homeodomain Transcription Factor

Abstract: Embryonic development of the pancreas is marked by an early phase of dramatic morphogenesis, in which pluripotent progenitor cells of the developing pancreatic epithelium give rise to the full array of mature exocrine and endocrine cell types. The genetic determinants of acinar and islet cell lineages are somewhat well defined; however, the molecular mechanisms directing ductal formation and differentiation remain to be elucidated. The complex ductal architecture of the pancreas is established by a reiterative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…Gu et al showed that pancreatic ducts emerge from Pdx1-expressing cells that separate from the endocrine and exocrine lineages between E9.5 and E11.5 (41). It has been demonstrated that non-islet Pdx1-positive cells display physical traits of ductal branching starting at E14.5, and there is even some evidence of these cells - which are insulin negative and K19 positive - as early as E12.5 (42). In addition, a 3D cell culture model of branching morphogenesis, using primary pancreatic duct cells, identified a transient surge of Pdx1 expression exclusive to branching cells (42).…”
Section: Regulation Of the Ductal Cell Lineage During Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu et al showed that pancreatic ducts emerge from Pdx1-expressing cells that separate from the endocrine and exocrine lineages between E9.5 and E11.5 (41). It has been demonstrated that non-islet Pdx1-positive cells display physical traits of ductal branching starting at E14.5, and there is even some evidence of these cells - which are insulin negative and K19 positive - as early as E12.5 (42). In addition, a 3D cell culture model of branching morphogenesis, using primary pancreatic duct cells, identified a transient surge of Pdx1 expression exclusive to branching cells (42).…”
Section: Regulation Of the Ductal Cell Lineage During Developmentmentioning
confidence: 99%
“…It has been demonstrated that non-islet Pdx1-positive cells display physical traits of ductal branching starting at E14.5, and there is even some evidence of these cells - which are insulin negative and K19 positive - as early as E12.5 (42). In addition, a 3D cell culture model of branching morphogenesis, using primary pancreatic duct cells, identified a transient surge of Pdx1 expression exclusive to branching cells (42). This suggests that Pdx1 might be involved temporally in a program of gene expression sufficient to facilitate the biochemical and morphological changes necessary for branching ductal morphogenesis, both during development and in the adult pancreas.…”
Section: Regulation Of the Ductal Cell Lineage During Developmentmentioning
confidence: 99%
“…Therefore, we have used a three-dimensional culture model of normal and cancer human bronchial epithelial cells (HBECs). Different studies have used a reconstituted Matrigel (BD Biosciences, Franklin Lakes, NJ, USA) derived from the Englebreth-Holm-Swarm tumour, composed of laminin, collagen IV and entactin, to study the morphology of human epithelial cell in three-dimensional culture from breast [11], intestine [12,13], pancreas [14,15] and metastatic tumour cells [16]. Lung epithelial cells from distal regions of rodent airways have also been shown to grow in Matrigel [17,18] and more recently in normal HBECs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Pdx1 is expressed in the foregut endoderm at E8.5 (Villasenor et al, 2008) and in both dorsal and ventral pancreatic buds by E9.5. By late gestation, Pdx1 expression becomes restricted to endocrine cells and later exclusively to β-cells (Guo et al, 2013;Wescott et al, 2009). Although Pdx1 is required for the expression of insulin, developmental targets are only now being identified (Khoo et al, 2012;Oliver-Krasinski et al, 2009;Raum et al, 2015).…”
Section: Introductionmentioning
confidence: 99%